2018
DOI: 10.1111/joop.12203
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of the origins of excessive work behaviour

Abstract: Studies of workers who engage in excessive work behaviour continue to attract the attention of researchers. Most research in this field adheres to quantitative methodologies aligned to the addiction or trait paradigms and largely focuses on correlates and consequences of such behaviour. However, within this literature, empirically based understandings of the factors that propel individuals to engage in excessive work patterns are sparse. Resting on socio‐cultural theories of work, we adopt a novel approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…Analysis continued with further iterations of discussion of themes and sub-themes with reference to the raw data, until a final set of themes were agreed. While it was not possible to calculate inter-rater agreement, trustworthiness of our approach is reinforced by ensuring that all interpretations are supported by raw data (Kirrane et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis continued with further iterations of discussion of themes and sub-themes with reference to the raw data, until a final set of themes were agreed. While it was not possible to calculate inter-rater agreement, trustworthiness of our approach is reinforced by ensuring that all interpretations are supported by raw data (Kirrane et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While it was not possible to calculate inter-CONCEPTUALIZING THE DISTINCTIVENESS OF TC 8 rater agreement, trustworthiness of our approach is reinforced by ensuring that all interpretations are supported by raw data(Kirrane et al, 2018).…”
mentioning
confidence: 99%
“…Importantly, case studies or other qualitative techniques used in the approaches of clinical psychology and systems could constitute raw preliminary data for further quantitative studies. For example, in a qualitative investigation of the origins of excessive work behavior, a participant invokes his early age experience of hard work (Kirrane et al., 2018): “ So even from an early age I was working. My father was a holy terror for work, work, work, work ” (p. 243).…”
Section: Diversified and Adequate Methodologiesmentioning
confidence: 99%
“…In addition, the Japanese corporate culture malpractice that is expected to lead to “karoshi” is known as “sabisu zangyo,” which means voluntary overtime. Overtime is supposed to be for unanticipated occasions in Western Europe, but in Japan, where the social value system exhorts “ganbaru” (to suffer in silence and to endure difficulties), it has become an expected part of daily duties that nobody can refuse (Kirrane, Breen, & O’Connor, 2018).…”
Section: The Systems Approachmentioning
confidence: 99%
“…As (work) behaviours always emerge embedded in the (work) context, qualitative field studies in real work contexts can especially contribute to an understanding of concrete work behaviours. As one of the few studies, a qualitative study of Kirrane, Breen, and O'Connor (2018) investigated the origins of excessive work behaviour and concluded that not only dispositional and socio-cultural factors of the employees but also organizational norms play a central role. A study of Janetzke and Ertel (2017) used a comparative case study design to investigate success factors for the implementation of a psychosocial risk management and identified not only personal but also structural and organizational cultural factors.…”
Section: Alternative Coping With Time and Performance Pressure: Limitmentioning
confidence: 99%